Hubungan Pendampingan Suami Dengan Kecemasan Ibu Primigravida Dalam Menghadapi Proses Persalinan Kala I Di UPT Puskesmas Kunir - Mauludiya, Melynda; Sunanto, Sunanto; Hidayati, Tutik (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
First-time mothers would have psychological changes such as high anxiety. To reduce anxiety during childbirth was the presence of a family, such as a husband. The presence of the husband would have a positive influence on the mother's physical readiness. The goal was to know The Relationship of Husband's attendant with Primigravida's Anxiety at the First Childbirth at Health Primary Care Centre Kunir Residence. The research design used a quantitative design that was correlation analytic, with approach cross sectional. The sample had 36 respondents. The sampling technique used simple random sampling. Statistical technique was correlation Chi Square test. The results of the study obtained 36 respondents there were 29 respondents (80,55%), accompanied by a husband, with a mild level of anxiety there were 16 respondents (44,44%), moderate anxiety was 13 respondents (36,11%), and 7 (19,44%) respondents that not accompanied by a husband has a severe level of anxiety. In correlation chi Square, The Relationship of Husband's attendant with Primigravida Mother's Anxiety in the First Childbirth has a significance value (ρ) which is 0.00 less than the value of α= 5% (ρ = 0.05), so that it means there was Relationship of Husband's attendant with Primigravida Mother's Anxiety in the First Childbirth